A probabilistic fuzzy analytic network process approach (PROFUZANP) in formulating sustainable manufacturing strategy infrastructural decisions under firm size influence. Issue 3 (3rd July 2018) - Ocampo, Lanndon
Abstract: This paper explores the probabilistic fuzzy analytic network process (PROFUZANP) approach in identifying the content of manufacturing strategy infrastructural decisions that attempt to integrate a sustainability and classical manufacturing strategy framework, in the presence of firm size as a relevant component in decision-making. Linguistic variables with equivalent triangular fuzzy numbers (TFNs) are used to elucidate the judgment of elements in pairwise comparison in the framework of the analytic network process (ANP). The ANP effectively handles the complexity of decision-making brought about by the subjectivity and relationships among components of the decision model. Integration of expert judgments conducted by introducing a normal probability distribution in each pairwise comparison with mean equal to the geometric mean of the judgment and standard deviation equal to a predefined perturbation of judgment around the mean. Pre-selected experts in manufacturing strategy and sustainability were asked to elicit judgment in pairwise comparison. Results show that the content of the infrastructural decisions of manufacturing strategy remains constant regardless of the types of firm size. However, the priority of each decision to the goal, which can be translated as the priority of implementation of each policy, varies between large firms and SMEs. The main contribution of this paper is a novel approach that holistically captures the judgmental uncertainty of individual decision-makers and the uncertainty of group decision-making.